2018
DOI: 10.1155/2018/9538787
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Contrarotating Open Rotor Aerodynamic Interactions

Abstract: High efficiency and low fuel consumption make the contrarotating open rotor (CROR) system a viable economic and environmentally friendly powerplant for future aircraft. While the potential benefits are well accepted, concerns still exist with respect to the vibrations and noise caused by the aerodynamic interactions of CROR systems. In this paper, emphasis is placed on the detailed analysis of the aerodynamic interactions between the front and aft propellers of a puller CROR configuration. For the first step, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To understand how the torque ratio relates to the rotational speed of the output shafts and the geometry of the gearset, it is necessary to introduce the basic equations defining the operation of a differential planetary gearbox, Eqs. ( 19) to (23). The power (P) balance in a DPGB defined in Eq.…”
Section: Output Shafts Torque Ratio Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how the torque ratio relates to the rotational speed of the output shafts and the geometry of the gearset, it is necessary to introduce the basic equations defining the operation of a differential planetary gearbox, Eqs. ( 19) to (23). The power (P) balance in a DPGB defined in Eq.…”
Section: Output Shafts Torque Ratio Selectionmentioning
confidence: 99%
“…The potential performance benefits of a CROR relative to single propeller engines and conventional turbofans have been extensively discussed in the literature, from acoustic [11]- [19], aerodynamic [11], [15], [20]- [23] and operability [13], [20]…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, one of the most reliable research methods is the experimental method, however, it has one significant drawback -this is the high cost of research. It was shown in [21,22] that at the initial stage, it is possible and necessary to use numerical gas dynamics methods for conducting preliminary studies. TECHNOLOGY AUDIT AND PRODUCTION RESERVES -№ 1/1(51), 2020…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…Reference [7] reported that the front blades exhibited larger deformation than the rear ones, but the latter saw a significantly greater change in performance than the former. Reference [8] studied the aerodynamic interactions of a CRP through unsteady Reynolds-averaged Navier-Stokes (URANS) simulations and found that aerodynamic interactions were the result of the mutual effects of the blade tip vortices, and the aft propeller absorbed the energy of the front propeller and thus reduced the strength of its blade tip vortices. Reference [9] numerically calculated the unsteady flow field of contra-rotating open rotors using the URANS method, compared the calculation results under different incoming flow conditions, and analyzed the complex aerodynamic interactions between propellers, finding that axial flow contributed to the improvement of propfans' aerodynamic performance.…”
mentioning
confidence: 99%